A novel method to predict internal relative humidity in cementitious materials by 1H NMR. (February 2018) - Hu, Zhangli; Wyrzykowski, Mateusz; Scrivener, Karen; Lura, Pietro
Abstract: In sealed cementitious materials, the internal relative humidity (RH) decrease is mainly due to the water activity depression caused by menisci formation in partially-saturated pores. This process can be conveniently described with the evolution of the Kelvin radius. To obtain the Kelvin radius, a novel method based on the evolution of pore volumes quantified by 1 H nuclear magnetic resonance (NMR) and mercury intrusion porosimetry (MIP) was developed. This approach was validated against experimental results for cementitious materials with a range of water to cement ratios from 0.30 to 0.46. A comparison between the Kelvin radius calculated with this approach with a previously published method using data obtained from MIP and chemical shrinkage was presented. A sensitivity analysis for the new prediction method was performed using a bootstrapping technique.